Relevansi Keterampilan Proses Sains Dalam Pembelajaran IPA Tingkat Sekolah Dasar Dengan Materi Ajar Tematik Kelas IV Tema 2 - Halimatun Nisa; Miptah Parid; Arif Hidayat; Arif Mustofa (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2020)
The purpose of this study was conducted to analyze the scope of science teaching materials in class IV SD 2 theme. Science teaching materials in class VI SD 2 theme is expected to be able to give rise to the science process skills contained in children. The research method used in this study is the library research method, the data collection technique uses documentation techniques. Based on the energy-saving material contained in class IV textbook subtheme 2 the teacher is able to bring up the science process skills contained in students based on the activity contained in the material. With this process skills students are able to develop the abilities contained within themselves both physical abilities and mental abilities as an initial stage to improve the abilities possessed by students. These physical and mental abilities are basically possessed by students although they are still simple and need to be stimulated to show their true identity.